2021
DOI: 10.1177/0094582x211008156
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of For-Profit Higher Education on Brazilian Education

Abstract: For-profit private higher education in Brazil emerged in the 1970s through state incentives such as educational credit and tax exemptions. In its most recent configuration, the logic of investment funds that trade on the stock exchange controls the largest institutions. The management of investment funds inserts a new variable into the investment of financial resources. It requires reducing costs to maximize shareholder value, but this means delivering precarious educational quality. Governed by a logic of max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Huber, Gunderson, and Stephens (2020), analyzing data from 15 developed countries, have concluded that an increase in public spending on education reduces income inequality, and da Costa and Gartner (2017) have argued the same for spending on education and health for Brazil from 1995 to 2012. According to Medeiros and Souza (2013), however, the way in which public spending is generally allocated in Brazil does not play a role in reducing inequality because the allocation of public funds is determined by institutions created for the sole purpose of preserving the privileges of a small ruling elite (for more information see Almeida, 2022).…”
Section: Financialization and Inequality In Brazilmentioning
confidence: 99%
See 4 more Smart Citations
“…Huber, Gunderson, and Stephens (2020), analyzing data from 15 developed countries, have concluded that an increase in public spending on education reduces income inequality, and da Costa and Gartner (2017) have argued the same for spending on education and health for Brazil from 1995 to 2012. According to Medeiros and Souza (2013), however, the way in which public spending is generally allocated in Brazil does not play a role in reducing inequality because the allocation of public funds is determined by institutions created for the sole purpose of preserving the privileges of a small ruling elite (for more information see Almeida, 2022).…”
Section: Financialization and Inequality In Brazilmentioning
confidence: 99%
“…This study is designed to contribute to a better understanding of the consequences of the apparent paradox described by Lavinas (2017), who writes of a transition between a period that witnessed a rise in public spending on programs that sought to reduce inequality and universalize access to basic services (such as health and education) in Brazil during the twenty-first century and a period of greater financialization with regard to health and education sectors (see Almeida, 2022;Sestelo et al, 2017). One of the most widely used definitions of financialization was coined by Epstein (2005), who defines financialization as the increased role of financial institutions, markets, and actors in the management of domestic and international economies.…”
mentioning
confidence: 99%
See 3 more Smart Citations